Solitary median maxillary central incisor syndrome occurring together with oromandibular-limb hypogenesis syndrome type 1: a case report of this previously unreported combination of syndromes - JINDA LERTSIRIVORAKUL, & ROGER K. HALL (IAPD and Blackwell, 2008)
The absence of upper central incisors was first reported by Scott in 1958. In 1968, Fulstow published a case of the congenital absence of an upper central incisor occurring together with short stature, congenital heart disease, microcephaly, and scoliosis.